A 6S Implementation and Impact Assessment in the Housekeeping and Linen Department of Tertiary Care Hospital - Keerthana Sheshareddy (Sekolah Tinggi Manajemen IPMI, 2023)
In modern days, healthcare cost is increasing tenfold along with immense pressure on healthcare providers to reduce the cost, improve quality of service and safety, lessen waiting time and eliminate the errors in the system. 6S targets at optimizing the process by eliminating waste and uses visual aids to achieve efficiency at workplace. The study aims at assessing the changes that is attained with the implementation of 6S in housekeeping and linen department of a tertiary care hospital. A quantitative method of data collection was employed with the help of a questionnaire and checklist. Independent Paired t-test, descriptive statistics and Repeated Measures ANOVA (RM-ANOVA) was used to analyse the data obtained. The Paired t-test indicated all the five sections of the questionnaire was very statistically significant (<.001). The pre-implementation score for housekeeping department was 33.593% and post score was 91.406%. The score for linen department improved from 62.5% to 88.28%. The p-value for sort was .016 which is statistically significant, the p-value for Set in order was .064 which is greater than 0.05 that implies there is no statistical significance followed by shine, standardize, sustain and safety with p-value of <.001, <.001, .005 and .002 respectively which are statistically significant for housekeeping department. The p-value for sort, set in order and shine was found to be .251, .368, .156 respectively which tells that there is no statistically significant difference between the means. The p-value for standardize was .004, .022 for sustain and .002 for safety which is statistically significant.